Anode layer and fluoride ion secondary battery

JP7638592B2Active Publication Date: 2025-03-04HONDA MOTOR CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021030505
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-26
Publication Date
2025-03-04
Estimated Expiration
2041-02-26

AI Technical Summary

Benefits of technology

【0016】 本発明によれば、フッ化物イオン二次電池の放電容量を向上させることが可能な負極層を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638592000002
    Figure 0007638592000002
  • Figure 0007638592000003
    Figure 0007638592000003
  • Figure 0007638592000004
    Figure 0007638592000004
Patent Text Reader

Abstract

To provide a negative electrode layer which enables the increase in the discharge capacity of a fluoride ion secondary battery.SOLUTION: A negative electrode layer comprises: a negative electrode active material; a conductive assistant; and a solid electrolyte. The negative electrode active material contains a fluoride of lanthanoid doped with a fluoride of alkali earth metal. The conductive assistant contains a carbon material. The solid electrolyte contains at least one of BaCaF4 and SrCaF4. In the negative electrode layer, the fluoride of lanthanoid doped with a fluoride of alkali earth metal and the carbon material are made a composite.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode layer and a fluoride ion secondary battery. [Background technology]

[0002] Lithium ion secondary batteries have been widely used as secondary batteries having high energy density. A lithium ion secondary battery has a separator disposed between a positive electrode and a negative electrode, and is filled with an electrolyte.

[0003] The electrolyte solution of a lithium ion secondary battery usually contains a flammable organic solvent, and therefore, there have been cases where thermal safety has been a problem.

[0004] In view of this, fluoride ion secondary batteries have been considered as all-solid-state batteries in which a solid electrolyte layer is disposed between a positive electrode layer and a negative electrode layer.

[0005] Lanthanide fluorides have a low defluorination potential, and therefore their use as negative electrode active materials in fluoride ion secondary batteries has been considered.

[0006] For example, a fluoride ion secondary battery having a metal lanthanide plate as a negative electrode current collector is known (for example, see Non-Patent Document 1). In this case, when the fluoride ion secondary battery is discharged, a lanthanide fluoride is generated on the metal lanthanide plate, and the lanthanide fluoride functions as a negative electrode active material. [Prior art documents] [Non-patent literature]

[0007] [Non-Patent Document 1] Adv. Funct. Mater. 2017, 27, 1701051 Summary of the Invention [Problem to be solved by the invention]

[0008] However, there is a problem in that the discharge capacity of the fluoride ion secondary battery is insufficient.

[0009] An object of the present invention is to provide a negative electrode layer capable of improving the discharge capacity of a fluoride ion secondary battery. [Means for solving the problem]

[0010] In one aspect of the present invention, an anode layer includes an anode active material, a conductive additive, and a solid electrolyte, the anode active material includes a lanthanoid fluoride doped with an alkaline earth metal fluoride, the conductive additive includes a carbon material, the solid electrolyte includes at least one of BaCaF4 and SrCaF4, and the lanthanoid fluoride doped with the alkaline earth metal fluoride and the carbon material are composited.

[0011] The lanthanide fluoride may be one or more compounds selected from the group consisting of LaF3, CeF3, SmF3 and NdF3.

[0012] The alkaline earth metal fluoride may be one or more compounds selected from the group consisting of CaF2, SrF2, and BaF2.

[0013] The lanthanide fluoride doped with the alkaline earth metal fluoride is La 0.9 Ba 0.1 F 2.9 , Ce 0.95 Ba 0.05 F 2.95 , Ce 0.95 Sr 0.05 F 2.95 and Ce 0.95 Ca 0.05 F 2.95 The compound may be one or more compounds selected from the group consisting of:

[0014] The solid electrolyte may include nanoparticles of at least one of BaCaF4 and SrCaF4.

[0015] Another embodiment of the present invention is a fluoride ion secondary battery having the above-described negative electrode layer, an electrolyte, and a positive electrode layer. Effect of the Invention

[0016] According to the present invention, it is possible to provide a negative electrode layer capable of improving the discharge capacity of a fluoride ion secondary battery. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a diagram showing the relationship of the ionic conductivity of Ce0.95Ba0.05F2.95 and CeF3 to the inverse of absolute temperature. [Diagram 2] FIG. 2 is a diagram showing initial charge / discharge curves of the all-solid-state fluoride ion secondary batteries of Example 1 and Comparative Example 1. [Diagram 3] FIG. 2 is a graph showing cycle characteristics of the all-solid-state fluoride ion secondary battery of Example 1. [Figure 4] FIG. 2 is a graph showing cycle characteristics of the all-solid-state fluoride ion secondary battery of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of the present invention will be described.

[0019] <Negative electrode layer> The negative electrode layer of this embodiment includes a negative electrode active material, a conductive assistant, and a solid electrolyte, and is used in a fluoride ion secondary battery. Here, the negative electrode active material includes a lanthanoid fluoride doped with an alkaline earth metal fluoride, the conductive assistant includes a carbon material, and the solid electrolyte includes at least one of BaCaF4 and SrCaF4. In addition, the lanthanoid fluoride doped with the alkaline earth metal fluoride and the carbon material are composited. That is, the negative electrode layer of this embodiment includes a composite of a lanthanoid fluoride doped with an alkaline earth metal fluoride and a carbon material (hereinafter, also referred to as a composite of a lanthanoid fluoride and a carbon material).

[0020] The negative electrode layer of this embodiment contains a lanthanoid fluoride doped with an alkaline earth metal fluoride, and therefore the ion conductivity is improved. In addition, the negative electrode layer of this embodiment contains a composite of a lanthanoid fluoride and a carbon material, and therefore the electronic conductivity is improved. Furthermore, the negative electrode layer of this embodiment contains at least one of BaCaF4 and SrCaF4, and therefore the defluorination potential is low. Therefore, when the negative electrode layer of this embodiment is applied to an all-solid-state fluoride ion secondary battery, the discharge capacity is improved.

[0021] [Negative electrode active material] The negative electrode active material includes a lanthanide fluoride doped with an alkaline earth metal fluoride.

[0022] The lanthanoid fluoride is not particularly limited, but examples thereof include LaF3, CeF3, SmF3, and NdF3, and two or more of them may be used in combination.

[0023] The alkaline earth metal fluoride with which the lanthanoid fluoride is doped is not particularly limited as long as it has ion conductivity. Examples of the alkaline earth metal fluoride include CaF2, SrF2, BaF2, etc., and two or more of them may be used in combination.

[0024] Examples of lanthanide fluorides doped with alkaline earth metal fluorides include La 0.9 Ba 0.1 F 2.9 , Ce 0.95 Ba 0.05 F 2.95 , Ce 0.95 Sr 0.05 F 2.95 , Ce 0.95 Ca 0.05 F 2.95 and the like, and two or more of them may be used in combination.

[0025] The negative electrode active material may further include a negative electrode active material other than a lanthanide fluoride doped with an alkaline earth metal fluoride.

[0026] The negative electrode active material other than the lanthanoid fluoride doped with the alkaline earth metal fluoride is not particularly limited as long as it is a negative electrode active material used in a fluoride ion secondary battery.

[0027] [Conductive additive] The conductive assistant includes a carbon material, and the carbon material may be carbon black.

[0028] Examples of carbon black include furnace black, ketjen black, and acetylene black, and two or more of these may be used in combination. The conductive assistant may further include a conductive assistant other than the carbon material. The conductive assistant other than the carbon material is not particularly limited as long as it is a conductive assistant used in a fluoride ion secondary battery.

[0029] [Lanthanoid fluoride-carbon composite] In the composite of a lanthanoid fluoride and a carbon material, for example, at least a part of the surface of a lanthanoid fluoride particle is coated with a carbon material.

[0030] The particle size of the composite of the lanthanoid fluoride and the carbon material is preferably 10 μm or less, and more preferably 5 μm or less. When the particle size of the composite of the lanthanoid fluoride and the carbon material is 10 μm or less, the ionic conductivity and the electronic conductivity are improved.

[0031] The mass ratio of the carbon material to the lanthanoid fluoride doped with the alkaline earth metal fluoride is preferably 3% by mass or more and 20% by mass or less, from the viewpoint of the balance between ionic conductivity and electronic conductivity.

[0032] The content of the composite of lanthanoid fluoride and carbon material in the negative electrode layer of this embodiment is preferably 60% by mass or more and 70% by mass or less. When the content of the composite of lanthanoid fluoride and carbon material in the negative electrode layer of this embodiment is 60% by mass or more and 70% by mass or less, the discharge capacity is improved when the negative electrode layer of this embodiment is applied to an all-solid-state fluoride ion secondary battery.

[0033] [Method for producing a composite of lanthanide fluoride and carbon material] A method for producing a composite of a lanthanoid fluoride and a carbon material (hereinafter also referred to as the composite) includes a first step of obtaining a lanthanoid fluoride-alkaline earth metal fluoride mixed powder, a second step of mixing the lanthanoid fluoride-alkaline earth metal fluoride mixed powder with a carbon material to obtain a composite precursor, and a third step of calcining the composite precursor to obtain the composite.

[0034] The first step is to mix a lanthanoid fluoride with an alkaline earth metal fluoride to obtain a lanthanoid fluoride-alkaline earth metal fluoride mixed powder. That is, by mixing a lanthanoid fluoride with an alkaline earth metal fluoride, the solid-phase diffusion distance of elements derived from the lanthanoid fluoride and the alkaline earth metal fluoride can be shortened during firing. In addition, after firing, a lanthanoid fluoride-alkaline earth metal fluoride mixed powder is obtained in which the crystal structure of the lanthanoid fluoride and the alkaline earth metal fluoride does not remain.

[0035] The method for mixing the lanthanoid fluoride and the alkaline earth metal fluoride is not particularly limited, and either a dry method or a wet method may be used. For example, a method in which the mixture is mixed using a mortar may be used.

[0036] The conditions, such as temperature and time, for mixing the lanthanoid fluoride and the alkaline earth metal fluoride can be appropriately set.

[0037] In the first step, the lanthanoid fluoride-alkaline earth metal fluoride mixed powder may be pulverized.

[0038] The lanthanide fluoride-alkaline earth metal fluoride mixed powder may be pulverized, for example, by using a ball mill.

[0039] The second step is a step of mixing the lanthanoid fluoride-alkaline earth metal fluoride mixed powder obtained in the first step with a carbon material to obtain a composite precursor.

[0040] In the method for producing the composite, the second step is carried out prior to the third step, in which the lanthanide fluoride-alkaline earth metal fluoride mixed powder is mixed with the carbon material in advance, thereby obtaining a composite precursor in which the carbon material is disposed on the surface of the lanthanide fluoride-alkaline earth metal fluoride mixed powder.

[0041] Therefore, by calcining the composite precursor in the third step, a composite is obtained in which at least a part of the surface of the lanthanoid fluoride particles doped with the alkaline earth metal fluoride is coated with the carbon material.

[0042] Furthermore, by disposing a carbon material on the surface of the lanthanide fluoride-alkaline earth metal fluoride mixed powder in the second step, coarsening of the particle size due to grain growth of the lanthanide fluoride-alkaline earth metal fluoride mixed powder and fusion of particle interfaces during the crystallization process in the third step can be suppressed, and a composite can be obtained that roughly maintains the particle size of the lanthanide fluoride-alkaline earth metal fluoride mixed powder.

[0043] In the second step, the method for mixing the lanthanide fluoride-alkaline earth metal fluoride mixed powder with the carbon material is not particularly limited, and either a dry method or a wet method may be used. For example, a method of mixing using a mortar may be used.

[0044] When the lanthanoid fluoride-alkaline earth metal fluoride mixed powder and the carbon material are mixed, it is preferable to apply shear.

[0045] The conditions such as the temperature for mixing the lanthanoid fluoride-alkaline earth metal fluoride mixed powder with the carbon material can be appropriately set.

[0046] Furthermore, in the second step, the composite precursor may be pulverized.

[0047] Examples of the method for pulverizing the composite precursor include a method for pulverizing using a ball mill and a method for pulverizing using a mortar.

[0048] The third step is a step of calcining the composite precursor obtained in the second step to obtain a composite.

[0049] In the second step, a composite precursor in which a carbon material is disposed on the surface of the lanthanide fluoride-alkaline earth metal fluoride mixed powder is obtained, and by doing so, the grain growth of the lanthanide fluoride-alkaline earth metal fluoride mixed powder and coarsening of the grain size due to fusion of the grain interfaces during the crystallization process in the third step are suppressed, resulting in a composite that roughly maintains the grain size of the composite precursor.

[0050] The conditions for firing the composite precursor can be appropriately set.

[0051] In the third step, the complex may be pulverized.

[0052] The method for pulverizing the complex may be, for example, a method in which the complex is pulverized using a mortar.

[0053] [Solid electrolyte] The solid electrolyte contains at least one of BaCaF4 and SrCaF4, and preferably contains nanoparticles of at least one of BaCaF4 and SrCaF4. This makes it easier to ensure an ion conduction path, and improves the discharge capacity when the negative electrode layer of this embodiment is applied to an all-solid-state fluoride ion secondary battery.

[0054] The particle size of the nanoparticles of at least one of BaCaF4 and SrCaF4 is, for example, 30 nm or more and 200 nm or less.

[0055] The mass ratio of the total amount of BaCaF4 and SrCaF4 to cerium fluoride doped with an alkaline earth metal fluoride is preferably 0.36 or more and 0.92 or less in terms of the balance between ion conductivity and defluorination potential.

[0056] The solid electrolyte may further include a solid electrolyte other than BaCaF4 and SrCaF4.

[0057] The solid electrolyte other than BaCaF4 and SrCaF4 is not particularly limited as long as it is a solid electrolyte used in a fluoride ion secondary battery.

[0058] <Fluoride ion secondary battery>

[0059] The fluoride ion secondary battery of this embodiment has the negative electrode layer of this embodiment, an electrolyte, and a positive electrode layer.

[0060] [Electrolyte] The electrolyte may be an electrolytic solution, a solid electrolyte, or a gel electrolyte. The solid electrolyte or gel electrolyte may be either organic or inorganic.

[0061] As the solid electrolyte, a known solid electrolyte can be used. For example, the solid electrolyte contained in the negative electrode layer of the present embodiment may be used as the solid electrolyte.

[0062] When a solid electrolyte is used as the electrolyte, the fluoride ion secondary battery of this embodiment is an all-solid-state fluoride ion secondary battery, which includes, for example, a positive electrode collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode collector, which are arranged in this order.

[0063] [Positive electrode layer] The positive electrode layer includes, for example, a positive electrode active material, a solid electrolyte, and a conductive additive. In this case, it is preferable to use a positive electrode layer that can obtain a sufficiently high standard electrode potential compared to the standard electrode potential of the negative electrode layer of this embodiment.

[0064] Examples of the positive electrode active material include Pb, Cu, Sn, Bi, and Ag.

[0065] Examples of solid electrolytes include PbSnF4 and Ce. 1-x Ba x F 3-x etc.

[0066] The conductive assistant may be, for example, a carbon material.

[0067] [Positive and negative electrode current collectors] Examples of the positive electrode current collector include a lead plate, an aluminum foil, etc. Examples of the negative electrode current collector include a gold foil, etc. EXAMPLES

[0068] Examples of the present invention will be described below, but the present invention is not limited to these examples.

[0069] [Example 1] An all-solid-state fluoride ion secondary battery was fabricated by the following method. Unless otherwise specified, each step was carried out in a purged glove box DBO-1.5B (manufactured by Miwa Manufacturing Co., Ltd.) equipped with an argon gas circulation purification device.

[0070] [Ce 0.95 Ba 0.05 F 2.95 -Preparation of AB complex] (1st step) 8.598 g of CeF3 powder (Sigma-Aldrich; purity 99.99%) and 0.402 g of BaF2 powder (High Purity Chemical Laboratory; purity 99.9%) were weighed out and mixed for 5 to 10 minutes using an agate mortar and pestle to obtain a CeF3-BaF2 mixed powder.

[0071] The CeF3-BaF2 mixed powder and 20 silicon nitride grinding balls (manufactured by Fritsch) with a diameter of 10 mm were placed in an 80 cc silicon nitride ball mill pot, a Premium Line PL-7 dedicated container (manufactured by Fritsch), and then sealed.

[0072] The sealed ball mill pot was taken out of the glove box, and then the powder was ground using a ball mill under the following conditions:

[0073] Rotational speed: 800 rpm Grinding time: 60 minutes Number of grinding processes: 40 Rest time between grinding processes: 5 minutes Rotation reverse: ON

[0074] After the ball mill pot was carried into the glove box, the CeF3-BaF2 mixed powder was collected from inside the ball mill pot.

[0075] (2nd process) Using an agate mortar and pestle, 500 mg of CeF3-BaF2 mixed powder was mixed with 36 mg of Denka Black (manufactured by Denki Kagaku Kogyo Co., Ltd.) as acetylene black (AB). 0.95 Ba 0.05 F 2.95 -AB complex precursor was obtained.

[0076] Ce 0.95 Ba 0.05 F 2.95 The -AB composite precursor, 20 zirconia grinding balls (manufactured by Fritsch) having a diameter of 10 mm, and 20 silicon nitride grinding balls (manufactured by Fritsch) having a diameter of 10 mm were placed in a Premium Line PL-7 dedicated container (manufactured by Fritsch) as an 80 cc silicon nitride ball mill pot, and then the container was sealed.

[0077] The sealed ball mill pot was taken out of the glove box, and then the powder was ground using a ball mill under the following conditions:

[0078] Rotational speed: 800 rpm Grinding time: 60 minutes Number of grinding processes: 40 Rest time between grinding processes: 5 minutes Rotation reverse: ON

[0079] After the ball mill pot was brought into the glove box, Ce was extracted from inside the ball mill pot. 0.95 Ba 0.05 F 2.95 The Ce-AB complex precursor was recovered. 0.95 Ba 0.05 F 2.95 The -AB complex precursor was ground for 5-10 minutes using an agate mortar and pestle.

[0080] (3rd step) Ce 0.95 Ba 0.05 F 2.95 The -AB composite precursor was transferred to an alumina crucible and then fired in a small electric furnace KSL-1100X (manufactured by MTI) to obtain Ce. 0.95 Ba 0.05 F 2.95 The sintering conditions were as follows:

[0081] Argon gas flow rate: 300cc / min Heating rate: 184℃ / h Maximum temperature reached: 1100℃ Hold time at maximum temperature: 1 hour Temperature drop rate: Uncontrolled Cooling method: natural cooling

[0082] From inside the alumina crucible, Ce 0.95 Ba 0.05 F 2.95The -AB complex was collected and then ground for 5 to 10 minutes using an agate mortar and pestle.

[0083] [Preparation of BaCaF4] (Premix) 690 mg of barium fluoride powder (manufactured by Kojundo Chemical Laboratory; purity 99%) and 310 mg of calcium fluoride powder (manufactured by Kojundo Chemical Laboratory; purity 99.9%) were weighed out and then premixed for about 1 hour using an agate mortar and pestle to obtain a BaF2-CaF2 mixed powder.

[0084] (Aerosol Process) The sealed powder hopper containing the BaF2-CaF2 mixed powder was taken out of the glove box and then connected to a high-frequency induction thermal plasma nanoparticle synthesis device TP-40020NPS (manufactured by JEOL Ltd.).

[0085] Argon gas was supplied to the plasma torch, and the BaF2-CaF2 mixed powder was melted by thermal plasma to form a BaF2-CaF2 melt, which was then sprayed into a chamber in a reduced pressure environment. The BaF2-CaF2 melt sprayed into the chamber was cooled and nano-sized to become BaCaF4. Next, BaCaF4 was collected by an exhaust filter downstream of the device. Next, the upstream and downstream of the exhaust filter were blocked by valves, and the filter was carried into a glove box to collect BaCaF4.

[0086] [Preparation of powder composition for negative electrode layer] Ce 0.95 Ba 0.05 F 2.95 536 mg of the -AB complex, 4464 mg of BaCaF, and 40 g of silicon nitride grinding balls (manufactured by Fritsch) having a diameter of 2 mm were placed in a 45 cc silicon nitride ball mill pot (manufactured by Fritsch), a container exclusively for the Premium Line PL-7, and then sealed.

[0087] The sealed ball mill pot was taken out of the glove box, and then the powder was ground using a ball mill under the following conditions:

[0088] Rotational speed: 200 rpm Grinding time: 15 minutes Number of grinding processes: 10 Rest time between grinding processes: 5 minutes Rotation reverse: ON

[0089] The ball mill pot was carried into the glove box, and then the powder composition for the negative electrode layer was collected from inside the ball mill pot.

[0090] [Preparation of powder for positive electrode layer (PbSnF4-AB composite)] 63.7% by mass of lead fluoride powder (manufactured by Kojundo Chemical Co., Ltd.), 29.6% by mass of tin fluoride powder (manufactured by Kojundo Chemical Co., Ltd.), and 6.7% by mass of acetylene black (manufactured by Denka Co., Ltd.) were mixed in a ball mill and then fired at 400°C for 1 hour in an argon atmosphere to produce a PbSnF4-AB composite.

[0091] [Powder for solid electrolyte layer] As the powder for the solid electrolyte layer, BaCaF4 used in preparing the powder composition for the negative electrode layer was used.

[0092] [Fabrication of all-solid-state fluoride-ion secondary batteries] A cylindrical pellet-type cell was produced by pressing the cells at a pressure of 40 MPa using a tablet press. Specifically, a 20 μm thick gold foil (manufactured by Nilaco; purity 99.99%) as a negative electrode current collector, 10 mg of a powder composition for a negative electrode layer, 40 mg of powder for a solid electrolyte layer, 20 mg of powder for a positive electrode layer, a 200 μm thick lead plate (manufactured by Nilaco; purity 99.99%) as a positive electrode active material and positive electrode current collector, and a 20 μm thick aluminum foil (manufactured by Nilaco; purity 99+%) as a positive electrode current collector were put into the tablet press in this order to produce a pellet-type cell.

[0093] [Comparative Example 1] An all-solid-state fluoride ion secondary battery was produced in the same manner as in Example 1, except that the powder composition for the negative electrode layer was produced as follows.

[0094] [Preparation of powder composition for negative electrode layer] 500 mg of CeF3 powder (Sigma-Aldrich; purity 99.99%), 36 mg of Denka Black (Denka) as AB, 464 mg of BaCaF4, and 40 g of silicon nitride grinding balls (Fritsch) with a diameter of 2 mm were placed in a 45 cc silicon nitride ball mill pot (Fritsch) dedicated to the Premium Line PL-7 container, and then sealed.

[0095] The sealed ball mill pot was taken out of the glove box, and then the powder was ground using a ball mill under the following conditions:

[0096] Rotational speed: 200 rpm Grinding time: 15 minutes Number of grinding processes: 10 Rest time between grinding processes: 5 minutes Rotation reverse: ON

[0097] The ball mill pot was carried into the glove box, and then the powder composition for the negative electrode layer was collected from inside the ball mill pot.

[0098] [Powder particle size] (Ce 0.95 Ba 0.05 F 2.95 -AB complex particle size) The powder was photographed using a scanning electron microscope SU-6600 (Hitachi High-Technologies Corporation), and the length of the powder in the SEM images of multiple fields of view was measured and used as the particle size.

[0099] (Particle size of BaCaF4) The specific surface area of ​​the powder was measured using a fully automatic specific surface area measuring device Macsorb HM model-1208 (manufactured by Mountec), and then the particle size was calculated from the specific surface area and true density of the powder.

[0100] As a result, Ce 0.95 Ba 0.05 F 2.95 The particle sizes of the -AB complex and BaCaF4 were 50 μm and 110 nm, respectively.

[0101] [Ce 0.95 Ba 0.05 F 2.95 and ionic conductivity of CeF3] A cylindrical pellet-type cell was produced by pressing the powder at a pressure of 40 MPa using a tablet press. 0.95 Ba 0.05 F 2.95 Next, the impedance analyzer 1255B / 1296A (Sotralon) was used to measure the CeF3 by AC impedance method. 0.95 Ba 0.05 F 2.95 and the ionic conductivity of CeF3 was measured. In Example 1, the composite of the negative electrode active material and the conductive additive was Ce. 0.95 Ba 0.05 F 2.95 -AB complex is used, so Ce 0.95 Ba 0.05 F 2.95 The ionic conductivity of CeF3 was compared with that of CeF3.

[0102] Figure 1 shows the relationship between the reciprocal of absolute temperature and Ce. 0.95 Ba 0.05 F 2.95 and the ionic conductivity of CeF3.

[0103] Also, in Table 1, Ce 0.95 Ba 0.05 F 2.95 4 shows the measurement results of the density and ionic conductivity of CeF3 at 140°C.

[0104] [Table 1]

[0105] From Figure 1 and Table 1, Ce 0.95 Ba 0.05 F 2.95 It can be seen that the ionic conductivity is higher than that of CeF3.

[0106] [Charge / discharge test] A constant current charge / discharge test was carried out on the all-solid-state fluoride ion secondary battery. Specifically, a potentiogalvanostat device SI1287 / 1255B (manufactured by Solartron) was used to carry out a constant current charge / discharge test in a vacuum environment at 140°C, with a charge / discharge current of 0.04mA, a lower limit voltage of -2.7V, and an upper limit voltage of -0.5V.

[0107] FIG. 2 shows the initial charge / discharge curves of the all-solid-state fluoride ion secondary batteries of Example 1 and Comparative Example 1.

[0108] It can be seen from FIG. 2 that the all solid-state fluoride ion secondary battery of Example 1 has a higher charge / discharge capacity than the all solid-state fluoride ion secondary battery of Comparative Example 1.

[0109] [Cycle test] A cycle test of the all-solid-state fluoride ion secondary battery was carried out. Specifically, a constant current charge / discharge test of the all-solid-state fluoride ion secondary battery was carried out five consecutive cycles in the same manner as described above.

[0110] 3 and 4 show the cycle characteristics of the all-solid-state fluoride ion secondary batteries of Example 1 and Comparative Example 1, respectively.

[0111] 3 and 4 show that the all solid-state fluoride ion secondary battery of Example 1 has a higher discharge capacity than the all solid-state fluoride ion secondary battery of Comparative Example 1.

Claims

1. The negative electrode comprises a negative electrode active material, a conductive additive, and a solid electrolyte, the negative electrode active material comprises a lanthanide fluoride doped with an alkaline earth metal fluoride; The conductive assistant contains a carbon material, The solid electrolyte is BaCaF 4 and SrCaF 4 At least one of the lanthanide fluoride doped with the alkaline earth metal fluoride and the carbon material are composited together; a content of the composite lanthanoid fluoride doped with alkaline earth metal fluoride and the carbon material is 60% by mass or more and 70% by mass or less;

2. The lanthanide fluoride is LaF 3 , CeF 3 , SmF 3 and NdF 3 The negative electrode layer according to claim 1 , wherein the negative electrode layer is one or more compounds selected from the group consisting of:

3. The alkaline earth metal fluoride is CaF 2 , SrF 2 and BaF 2 The negative electrode layer according to claim 1 or 2, which is one or more compounds selected from the group consisting of:

4. The lanthanide fluoride doped with the alkaline earth metal fluoride is La 0.9 Ba 0.1 F 2.9 , Ce 0.95 Ba 0.05 F 2.95 , Ce 0.95 Sr 0.05 F 2.95 and Ce 0.95 Ca 0.05 F 2.95 The negative electrode layer according to claim 1 , wherein the negative electrode layer is one or more compounds selected from the group consisting of:

5. The solid electrolyte is BaCaF 4 and SrCaF 4 The negative electrode layer according to claim 1 , comprising nanoparticles of at least one of:

6. A fluoride ion secondary battery comprising the anode layer according to claim 1 , an electrolyte, and a cathode layer.

Citation Information

Patent Citations

  • Fluoride ion battery and method for manufacturing the same

    JP2018077986A

  • Fluoride ion all solid state battery

    JP2018092863A

  • Method for producing solid electrolyte and solid electrolyte for electrode

    JP2020091967A